2022
DOI: 10.1109/access.2022.3160230
|View full text |Cite
|
Sign up to set email alerts
|

Games and Rewards: A Scientometric Study of Rewards in Educational and Serious Games

Abstract: In this study we provide a new viewpoint on the body of literature regarding rewards in serious and educational games. The study includes a quantitative bibliometric analysis of literature in this context from 1969 to 2020. The dataset from the Scopus abstract and citation database was analyzed with the Bibliometrix R library. The data set was manually cleaned to contain only the relevant articles and conference papers. The data was then categorized to match the common themes. From the remaining documents, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 32 publications
0
10
0
1
Order By: Relevance
“…The subjects that appear most frequently in this dataset include gamification, exercise, health, game design, and game-based learning. The literature emphasizes theory instead of actual application [50]. It assists those involved in creating educational policies and gamification-based software firms and organizations in determining the gamification strategies that work best for online learning [51].…”
Section: Previous Studies and Research Gapmentioning
confidence: 99%
“…The subjects that appear most frequently in this dataset include gamification, exercise, health, game design, and game-based learning. The literature emphasizes theory instead of actual application [50]. It assists those involved in creating educational policies and gamification-based software firms and organizations in determining the gamification strategies that work best for online learning [51].…”
Section: Previous Studies and Research Gapmentioning
confidence: 99%
“…The reward types used in the most popular mobile phone games is a largely unexplored research field. Not much literature can be found that examines the reward types used in the mobile game context, unlike gamification, which is the most popular segment of research in the field of reward systems [7]. Most rewards used in gamification studies are badges, tangible rewards, currency, unspecified rewards, likes, animated feedback and kudos [34].…”
Section: A Reward Typesmentioning
confidence: 99%
“…Regarding future research in the field of reward systems, we suggest adding data points by explaining how the rewards were obtained, in addition to expanding the reward typology presented in [26] into relevant subcategories. We encourage research in the field of reward types and systems in contexts other than gamification (as it appears to be the most popular one [7]). The duration of gaming sessions in the different games could be taken as a data point for comparison with [22].…”
Section: Future Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Considerando que, una mejora en los niveles de habilidades blandas socioemocionales tiene un efecto directo sobre la motivación de los estudiantes (Tseng, et al, 2018); (Feraco T. et al, 2022); Mishra & Sahoo, 2022;Feraco T. et al, 2023), en este trabajo se pretende cuantificar si los niveles de habilidades antes del entrenamiento son diferentes en su efecto sobre la motivación después del entrenamiento. Diversos estudios han constatado que una adecuada motivación extrínseca, basando la estrategia de aprendizaje a través de metodologías como la gamificación (Partovi, & Razavi, 2019), los juegos con recompensas (Tyni et al, 2022;Cespón, & Lage, 2022), el aprendizaje-servicio (Lo et al, 2022), entre otras, aumenta el rendimiento de los estudiantes, así como su grado de satisfacción. Sin embargo, un componente relevante sobre la propia estrategia de aprendizaje del estudiante que no se está considerando en las aulas universitarias es la que se realiza a través de su motivación intrínseca y los factores asociados a su propio autoconocimiento y habilidades socioemocionales, como la empatía y la compasión (Feraco et al, 2022(Feraco et al, , 2023.…”
Section: Introductionunclassified